An annotated checklist of sucking lice (Phthiraptera: Anoplura) from domestic and wild mammals in Malaysia, with lists of hosts and pathogens - Kazim, Abdul-Rahman; Houssaini, Jamal; Tappe, Dennis; Heo, Chong-Chin (Zootaxa, 2022)
Literature records of sucking lice (Phthiraptera: Anoplura) from Malaysia were checked and reviewed, resulting in a list of 34 established species belonging to 11 genera (Ancistroplax, Atopophthirus, Enderleinellus, Haematopinus, Hamophthirius, Hoplopleura, Linognathus, Neohaematopinus, Pedicinus, Polyplax and Sathrax). Furthermore, three local and six cosmopolitan louse species are regarded as dubious in Malaysia, due to misidentifications or lack of locality records. Also, pathogens known to be associated with the sucking lice are listed. The alarming conservation status of some Malaysian mammalian host species and their sucking lice warrant more research and imminent action to preserve the biodiversity of the country. This paper presents the first complete checklist of anopluran lice from both Peninsular Malaysia and Malaysian Borneo, including localities, literature references and a host-louse list.